The Effect Of Good Corporate Governance On Tax Avoidance In Mining Corporate Listed On The Idx For The Period 2013-2017 - et. al., Rina Tresnawati, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to examine the effect of Good Corporate Governance on Tax Avoidance. The population in this study are all Mining companies listed on the Indonesia Stock Exchange in the period 2013-2017. The population in this study consisted of 39 mining companies. The research method used in this research is explanatory research. The sampling technique in this study used stratified random sampling and obtained 11 companies. The model in this study is path analysis using eviews 10. The results of this test indicate that the proxy for Good Corporate Governance, namely Institutional Ownership, Independent Board of Commissioners, Audit Committee and Audit Quality Significantly influence Tax Avoidance on Mining companies listed on the Indonesia Stock Exchange 2013-2017 period. The amount of influence significantly revealed Good Corporate Governance in this study amounted to 74.6%.